In Silico Analysis of Bioactive Compounds from Imperata cylindrica as Potential EGFR Inhibitors in Cervical Cancer - Muhammad Farid; Hanin Fitri Aqilanisa; Jihan Aqila Najwa Ulayya; Gylda Shareefa Carent Nissiara; Murni Ramadhani; Ardestya Rastrani (Sunan Kalijaga State Islamic University & Society for Indonesian Biodiversity, 2026)
Cervical cancer remains a major cause of death in women globally. Conventional treatments often result in toxicity and resistance, prompting interest in natural alternatives. Imperata cylindrica has demonstrated potential anticancer activity, but its molecular interaction with EGFR in cervical cancer remains unexplored. Objective This study employed an in-silico approach to evaluate the potential of bioactive compounds from I. cylindrica as epidermal growth factor receptor (EGFR) inhibitors. Methods: An in-silico study was conducted using molecular docking using AutoDock v4.2.6 to assess the binding affinity of I. cylindrica bioactive compounds toward EGFR. Docking validation used redocking. ADMET predictions were performed using pkCSM and ProTox-II to evaluate pharmacokinetics, toxicity, and drug-likeness properties. Results: Jatrorrhizine, curcumin, and 5-hydroxyflavone showed strong binding to EGFR (?G: –8.00 to –7.67 kcal/mol) with key interactions at Asp855 and Lys745. These compounds also exhibited good oral absorption and low toxicity. Arundoin showed the highest affinity (–8.57 kcal/mol) but poor ADMET characteristics, reducing its therapeutic potential. Conclusion: Jatrorrhizine, curcumin, and 5-hydroxyflavone show potential as EGFR inhibitors, warranting further experimental validation and development.